The Holocoust Tragedy in John Boyne “The Boy In The Striped Pajamas” - Nida Mashlahatul Khoiriyah; Anita Rahmah Dewi (JELP Journal of English Language and Pedagogy, 2022)
The Holocaust is a massacre tragedy in World War II which resulted in more than 7 people died. The massacre was carried out by the Germans against the Jews, where the Germans considered the Aryans to be the holiest tribes on earth. The tragedy of the Holocaust formed many perspectives of opinion and also got a lot of pros and cons. Therefore, the author conducted research on the Holocaust of World War II on the propaganda aspect in “The Boy in the Striped Pajamas” novel . This is to get the results of the causes behind the Holocaust in World War II and the Holocaust propaganda itself. The research uses the Historical Approach in carrying out research, and uses the theory of New Historicism that was coined by Greenblatt. The method used is close-reading and data collection using note-taking, in which the source is obtained from accurate data. The results obtained from this study are a form of the author's concern for the science of the history of Holocaust propaganda, during World War II for the facts behind the Holocaust, as well as the impact that has occurred after the event in the present.